Global, regional, and national burden of digestive diseases: findings from the global burden of disease study 2019 - Wang, Fang; Hu, Dingtao; Sun, Hongyu; Yan, Ziye; Wang, Yuhua; Wang, Linlin; Zhang, Tingyu; Meng, Nana; Zhai, Chunxia; Zong, Qiqun; Hu, Wanqin; Yu, Guanghui; et al. (Frontiers in Public Health, 2023)
The global burden of digestive diseases has been rising in the last 30 years. The rates and trends of incidence, deaths, and disability-adjusted life-years (DALYs) for digestive diseases need to be investigated. We extracted the data on overall digestive diseases and by cause between 1990-2019 from the Global Burden of Diseases 2019 website, including the absolute number and the corresponding age-standardized rates of incidence (ASIR), deaths (ASDR), and DALYs (ASDALYs). Globally, the incident cases, deaths, and DALYs of digestive diseases in 2019 increased by 74.44%, 37.85%, and 23.46%, respectively, compared with that in 1990, with an increasing ASIR of 0.09%, as well as decreasing ASDR and ASDALYs of 1.38% and 1.32% annually.The sociodemographic index (SDI) of overall digestive diseases showed a slight increase in ASIR from low to middle-low regions. The downtrend in ASDR and ASDALYs was found in all SDI regions. The burden of incidence was higher in females, while the burden of deaths and DALYs was higher in males for the overall digestive diseases and most causes. The estimated annual percentage changes were significantly associated with the baseline ASIR, ASDR, and ASDALYs for the overall digestive diseases, and the negative correlations between ASDR, ASDALYs, and human development index both in 1990 (R=-0.68, R=-0.69) and 2019 (R=-0.71, R=-0.73) were noticed. The findings indicate that digestive diseases remain a significant public health burden, with substantial variation across countries, sexes, and age groups. Therefore, implementing age, gender, and country-specific policies for early screening and targeted interventions could significantly reduce the global burden of digestive diseases.